2008
DOI: 10.1002/cjg2.1292
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Daily Position Time Series from the Hong Kong Gps Fiducial Network

Abstract: Characteristics of daily position time series from January 2001 to August 2007 at 12 GPS stations in the Hong Kong GPS fiducial network are investigated. A spatial filtering algorithm based on principal component analysis is employed to remove the common mode errors from the daily position time series. The noise characteristics of the filtered position time series are assessed by the method of maximum likelihood estimation.Contributions from atmospheric, nontidal oceanic, snow and soil moisture mass loading ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 22 publications
4
35
0
1
Order By: Relevance
“…The processing includes the following corrections: ATML, SMML, NTOL and SCML based on QLM dataset (Yuan et al, 2008;Jiang et al, 2013;He et al, 2015). The QLM dataset described as follows (for me detail see Dong et al, 2002;Yuan et al, 2008;Jiang et al, 2013;He et al, 2015).…”
Section: Environmental Loading Dataset and Processingmentioning
confidence: 99%
“…The processing includes the following corrections: ATML, SMML, NTOL and SCML based on QLM dataset (Yuan et al, 2008;Jiang et al, 2013;He et al, 2015). The QLM dataset described as follows (for me detail see Dong et al, 2002;Yuan et al, 2008;Jiang et al, 2013;He et al, 2015).…”
Section: Environmental Loading Dataset and Processingmentioning
confidence: 99%
“…Many regional station networks have been established for monitoring the crust deformation and water vapor contents using global navigation satellite system (GNSS) Yuan et al 2008;Nilsson and Elgered 2008;Lee et al 2013;Ji et al 2014). The dominant noises in GNSS position time series are white, flicker and random walk noises Langbein and Johnson 1997;Mao et al 1999;Williams et al 2004;Langbein 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the spatiotemporal filtering using PCA, CME can be got with varying spatial responses, providing a more solid numerical framework for analyzing the physical source in the time series. Yuan et al (2008) found that the cycle items of CME got by PCA filtering in vertical direction decreased significantly after a load mass correction, suggesting that non-tectonic deformation is the main cause of CME in vertical direction. In addition, as an effective spatiotemporal analysis method, PCA has also been used in the field of earth geophysics for various purposes (Kawamura and Yamaoka 2006;Tiampo et al 2004).…”
Section: Introductionmentioning
confidence: 94%